Conception of socio-cultural identity in the modern theory of architecture - Blinova, Maria; Rodik, Yanina (Видавництво Львівської політехніки, 2013)
In this paper methodologically substantiate the study of the architectural environment of a modern city by its belonging to different socio-cultural communities as a cultural resource in situation of multiculturalism and globalization. The aim of the research was to provide rationalization for using the concept of socio-cultural identity as the key to system view on the problem of humanization of the modern city’s environment. The study concluded that the architectural environment should be seen as a major unifying force that opposes the trend of globalization and a major resource for the coexistence of the local socio-cultural differences.
Keywords: architectural environment; globalization; sociocultural identity; theory; sustainability